(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today world is facing many problems. People in 21st century are running after the money and materialist things. And today’s relationships are based on economy, individualism and greed. This change has begun to break the piousness of the social relationships. Children, youngster, can say all age group is influenced by the modernisation of the world. We are forgetting our tremendous culture of “Maryada Purushotam Shree Ram”. Ramayana upholds the concepts and principle and has the foundation of a family structure. Ramayana is a universal source of wisdom. Ramayana teaches us to live with harmony, love and affection, with others. We can take solutions of many problems from Ramayana. Because we can solve our problems with three ways, with the help of logic, with the help of evidence based life or experience, third with the help of Satvic Gyan or Sastra. Ramayana gives a portrayal of Indian culture. Ramayana tells us about all the enemy of individual’s it. Such as greed, moral degradation, callous, impoliteness, hostility ,cruel, and dishonesty, as well as good aspects of within the individuals, for example- bravery, calm, honesty, brotherhood, sacrifice, kindness, loyalty, morality, nobility and patients. Psychology is also related with the grate Epic Ramayana. Maslow said five hierarchical stages of human needs. First are physiological biological needs. Second safety need, third love belongingness need, forth esteem need, and last is self-actualization need. Lower four need are known as deficiency need. As human being fulfil his lower four needs, then he look after for self-actualisation need. Ramayana is based on self-actualisation need of psychology. Other psychologist named Freud told about 3 structure of human personality. Id, Ego and Superego. These three parts of personality combining form complex human behaviour. ID is regulated by pleasure principle. Id wants instant gratification of the need. ID is the basic part of personality. Babies are driven by this part, for example- baby cries until heshe is feed. Ego is based on reality principle. Ego deals with the id’s need in a socially acceptable manner. Superego deals with the morality. Superego develops last. And it is based on what is wrong and what is right. Superego driven person take hid decision based on moral values, which is the foundation of human society. In Ramayana “Maryada Purushotam Shree Ram” was depicted as a superego based human being. Who took all his decision on moral values. So we can say that Ramayana is best teacher for a human being.